Effect of Preoperative Education about Spinal Anaesthesia on Anxiety and Postoperative Outcomes in Parturients undergoing Elective Caesarean Section: An Interventional Study - Namitha Arun; Veena Nadarajan; Vimal Pradeep (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Pregnant women often experience anxiety due to myths and worries about surgery, particularly caesarean section, which are common during childbirth. Their anxiety can impact overall satisfaction, recovery, and mental health. Addressing these issues is crucial for improving both surgical outcomes and the childbirth experience. Aim: To assess the effectiveness of a preoperative education program utilising materials and videos on spinal anaesthesia in reducing anxiety and enhancing postoperative outcomes for patients undergoing caesarean section. Materials and Methods: An interventional study was conducted with 64 consecutive parturients who were divided into two equal groups, the study group (group A) and the control group (group B) at Government TD Medical College Alappuzha, Kerala, India. Group A received structured education on spinal anaesthesia, with individual questions and concerns addressed using the video and handbook. Group B received routine preoperative information. Preoperative anxiety was measured using Amsterdam Preoperative Anxiety and Information Scale (APAIS), while postoperative pain was assessed using Visual Analogue Scale (VAS) at 4, 12, and 24 hours after surgery. Data analysis was performed using Statistical Package for the Social Sciences (SPSS). Results were presented as frequencies for qualitative variables and as mean with standard deviation for quantitative variables. Statistical tests included Student’s t-test, Chi-square test, Fisher’s exact test, and paired t-test. Statistical significance was set at p-value<0.05. Results: Preoperative education led to statistically significant reductions in anxiety levels for each individual, pre-educational and post-educational mean APAIS scores were 18.06 and 13.66, respectively, which was statistically significant (p-value<0.001). The post-educational APAIS score (13.66) was lower than the mean APAIS score in the control group (20.31), which was statistically significant (p-value<0.001). Postoperative pain at 12 hours was significantly lower in the group that received the educational session compared to controls (p-value<0.04). Conclusion: Preoperative education on spinal anaesthesia significantly reduced anxiety and improved postoperative outcomes for parturients undergoing caesarean section. These findings highlight how well-planned education can enhance care for expectant mothers during childbirth.